THE EFFECT OF BUREAUCRATIC REFORM TO THE QUALITY OF PUBLIC SERVICES IN THE POPULATION AND CIVIL REGISTRATION OF SIKKA DISTRICT - Rangga, Yoseph Darius purnama; Kurniawan Gheta, Antonius Philipus (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to determine whether bureaucratic reform has an influence on the quality of public services in the Population and Civil Registry Office of SIKKA Regency. This research is a descriptive study with a quantitative approach. The sample in this study amounted to 33 people consisting of 4 officials including the head of the Office and 29 employees who work in the Office of Population and Civil Registry of Sikka Regency. The data collection techniques in this study used interview techniques, questionnaires and documentation. The results of this study indicate that the bureaucratic reform variable influences the quality of public services in the Office of Population and Civil Registry of Sikka Regency by 32.8%. Keywords: bureaucratic reform, quality of public services.